2015
DOI: 10.3389/fnhum.2014.01029
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem encoding of speech and musical stimuli in congenital amusia: evidence from Cantonese speakers

Abstract: Congenital amusia is a neurodevelopmental disorder of musical processing that also impacts subtle aspects of speech processing. It remains debated at what stage(s) of auditory processing deficits in amusia arise. In this study, we investigated whether amusia originates from impaired subcortical encoding of speech (in quiet and noise) and musical sounds in the brainstem. Fourteen Cantonese-speaking amusics and 14 matched controls passively listened to six Cantonese lexical tones in quiet, two Cantonese tones in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 106 publications
3
48
1
Order By: Relevance
“…In particular, the decoding of T4 was considerably less accurate than any of the other three tones. This result is in line with previous findings showing a suboptimal subcortical encoding of falling tonal patterns (Krishnan et al, 2010; Krishnan et al, 2009; Krishnan et al, 2004; Liu, Maggu, Lau, & Wong, 2015). For example, Krishnan et al (2010) used normalized autocorrelation to estimate the strength of periodicity in the FFR (peak autocorrelation metric).…”
Section: Discussionsupporting
confidence: 93%
“…In particular, the decoding of T4 was considerably less accurate than any of the other three tones. This result is in line with previous findings showing a suboptimal subcortical encoding of falling tonal patterns (Krishnan et al, 2010; Krishnan et al, 2009; Krishnan et al, 2004; Liu, Maggu, Lau, & Wong, 2015). For example, Krishnan et al (2010) used normalized autocorrelation to estimate the strength of periodicity in the FFR (peak autocorrelation metric).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a pitch mechanism reliant upon TFS remaining the primary mechanism in amusics, and with amusics performing better at pitch discrimination when TFS cues are available than when not, despite performing poorly compared to controls (Cousineau et al, 2015). Consistent with Cousineau et al (2015), and with Liu et al (2014) who found no evidence for the representation of pitch information being degraded at the level of the auditory brainstem in amusics, no evidence was found in the present study for a deficit in the peripheral representation of TFS in amusics (Fig. 2A).…”
Section: Amusics Are More Likely Than Controls To Use Envelope Pitch-supporting
confidence: 73%
“…Any mechanism for pitch-extraction is likely to reside beyond the superior olive, at or after the lateral lemniscus or the inferior colliculus (Gockel et al, 2011), suggesting that any TFS processing deficit associated with impaired pitch perception in amusia must reside at or central of this stage of the auditory brainstem. Consistent with this, a recent study has failed to find evidence of impaired pitch encoding in the rostral auditory brainstem as indicated by the frequency-following response (Liu et al, 2014, although see also Lehmann et al, 2015).…”
Section: Introductionmentioning
confidence: 56%
“…Various studies have converged in identifying the right inferior frontal cortex (BA47), right auditory cortex (BA22), and the arcuate fasciculus as potential sources of these abnormal electrical responses (Hyde, Zatorre, Griffiths, Lerch, & Peretz, 2006;Hyde, Zatorre, & Peretz, 2011;Loui, Alsop, & Schlaug, 2009), and recent evidence suggests that BA47 is responsible for amusics' abnormal P300 (Albouy, Schulze, et al, 2013). The centrality of these cortical mechanisms to amusia is supported by recent c o r t e x 6 9 ( 2 0 1 5 ) 1 8 6 e2 0 0 evidence that amusics show intact brainstem encoding of speech and music, as measured by the frequency following response (Liu, Maggu, Lau, & Wong, 2015). Therefore, TMS could be used to mimic amusic brain function in non-amusic participants by creating a transient lesion in BA47.…”
Section: Discussionmentioning
confidence: 93%